The Defence of the Military Posts of the Slovene Home Guard - Kladnik, Tomaž (Inštitut za novejšo zgodovino, 2006)
On the basis of the sources from the Archives of the Republic of Slovenia, the author deals with the defence of some sixty military posts of the Slovene Home Guard, which monitored the territory of the Ljubljana Province, especially its central area and the one along its communication infrastructure. The posts, both the residential buildings and those located at the entrance to larger settlements, were increasingly fortified because of the risk of attacks by the National Liberation Army and partisan detachments. Most posts were defended with field fortification systems. As a case study, the defence of the Velike Lašče military post is presented. The paper was written on the basis of the author's doctoral thesis entitled Slovensko vojaško šolstvo in vojaške operacije 1941-194S (Slovene Military Education and Military Operations 1941-1945). Avtor obravnava na podlagi arhivskih virov v Arhivu Republike Slovenije obrambo vojaških postojank Slovenskega domobranstva. To je iz okoli 60 postojank izvajalo nadzor ozemlja Ljubljanske pokrajine, predvsem njenega osrednjega dela in prostora vzdolž komunikacij. Postojanke so bile zaradi nevarnosti napadov NOV in PO Slovenije vedno bolj utrjene, tako bivalni objekti sami kot tudi dostopi v kraj. Večino postojank so branili s poljskimi fortifikacijskimi sistemi. Kot študijo primera je prikazal obrambo vojaške postojanke Velike Lašče. Članek je napisan na osnovi avtorjeve doktorske disertacije z naslovom Slovensko vojaško šolstvo in vojaške operacije (1941-1945).